A CASE REPORT OF SUSPECTED RARE ANOMALY AQUEDUCTAL STENOSIS BY WEB CAUSING HYDROCEPHALUS OBSTRUCTIVE IN PEDIATRIC - Alma Putri Maulidawati; Feda Anisah Makkiyah (The Health Researcher's Journal, 2026)
The aqueductal web is a rare congenital anomaly where a thin membrane obstructs the aqueduct of Sylvius, disrupting cerebrospinal fluid (CSF) flow and leading to obstructive hydrocephalus. This condition can be challenging to diagnosis, particularly in settings with limited access to advanced imaging. This report discusses a six-month-old male infant presenting with progressive head enlargement, vomiting, and irritability. A head CT scan revealed dilated lateral and third ventricles suggestive of obstructive hydrocephalus, likely caused by an aqueductal web. Due to limited access to MRI and endoscopic third ventriculostomy (ETV) facilities in the local healthcare setting, a ventriculoperitoneal (VP) shunt was chosen as the treatment. The patient underwent VP shunt placement, which successfully diverted excess CSF, reduced intracranial pressure, and improved clinical symptoms. Postoperative management included prophylactic antibiotics, with no significant complications observed apart from a localized hematoma. Early diagnosis and appropriate management of obstructive hydrocephalus due to the aqueductal web are essential to prevent long-term neurological damage. While MRI remains the gold standard for detailed diagnosis, CT remains crucial with limited resources. VP shun remains a reliable intervention in such settings, with good clinical outcomes when managed appropriately.